The association between fatty acid quality indices and quality of life among overweight and obese women: A cross-sectional study - Rasaei, Niloufar; Daneshzad, Elnaz; Soveid, Neda; Clark, Cain C. T.; Mirzaei, Khadijeh (Frontiers in Public Health, 2023)
Background: Decreased quality of life (QOL) is a major public health challenge, affecting the global population. Fatty acid quality indices (FAQI) are novel determinants of QOL and may have an impact on different aspects of QOL. Prior research has established a significant link between different dietary approaches and QOL. However, the association between FAQI and different dimensions of QOL has not been established. Therefore, we aimed to investigate the association between FAQI and the QOL in overweight and obese women. Methods: Totally, 378 adult overweight and obese women participated in this cross-sectional study. Several anthropometric indices, systolic and diastolic blood pressure, and biochemical factors were measured using standard protocols. Dietary intake was assessed by a validated and reliable semi-quantitative food frequency questionnaire (FFQ 147 items). FAQI was considered as the cholesterol-saturated fat index (CSI) and the ratio of omega-6/omega-3 (N6/N3) essential fatty acids. SF-36 questionnaires were utilized for judging QOL. Linear logistic regression was used, in crude and adjusted models, to evaluate the associations of FAQI and QOL. Results: The analytical sample included 279 participants for the ω-6/ω-3 ratio and 378 participants for CSI in the present study. The mean (±SD) age of the study population was 36.65¬ ± 9.07 years. Linear logistic regression analysis, with adjustment for potential confounders, such as age, energy intake, body mass index, job, and thyroid status, showed that ω-6/ω-3 was negatively and marginally significantly related to general health (B= -139.94, 95%CI: -286.54, 6.66; p=0.061) and role physical (B= -337.68, 95%CI: -679.99, 1.61; p=0.051). A significant negative association was found between the ω-6/ω-3 ratio and social functioning (B= -247.54, 95%CI: -458.14, -36.94; p=0.021), which means obese and overweight women with a greater ω-6/ω-3 ratio, have a lower social functioning score. Conclusions: It was found that FAQI was negatively associated with some QOL measurements in overweight and obese Iranian women, suggesting that greater abundance of fatty acids, especially trans and saturated fatty acids, may be associated with lower QOL.